1979
DOI: 10.2337/diab.28.11.1015
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Plasma Glucagon Concentration in Maturity-Onset Diabetics with Autonomic Neuropathy

Abstract: The mean fasting plasma immunoreactive glucagon (IRG) concentration in 25 non-insulin-dependent, maturity-onset diabetics (MODs) was 15.4 ± 3.1 pmol/L, which was not significantly different from the 16.8 ± 2.4 pmol/L in 17 normal controls of similar age. However, in seven MODs with autonomic neuropathy (AN) the mean fasting IRG concentration of 44.7 ± 4.4 was significantly greater than the 17.4 ±1.3 pmol/L in 18 MODs without neuropathy and compared with controls. We, therefore, investigated IRG concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…In the four previous studies that we are aware of that dealt with this issue, (3,(13)(14)(15), no consensus was reached concerning the appropriateness of counterregulatory hormone responses (3,(13)(14)(15). Furthermore, no data are presently available concerning changes in glucose production and glucose utilization or the ability to restore euglycemia.…”
Section: Introductionmentioning
confidence: 94%
“…In the four previous studies that we are aware of that dealt with this issue, (3,(13)(14)(15), no consensus was reached concerning the appropriateness of counterregulatory hormone responses (3,(13)(14)(15). Furthermore, no data are presently available concerning changes in glucose production and glucose utilization or the ability to restore euglycemia.…”
Section: Introductionmentioning
confidence: 94%
“…All papers concerning glucose counterregulatory hormone responses to hypoglycaemia in Type 2 DM were regarded eligible for evaluation in this review. We were able to retrieve 16 research articles [23–37,39], the characteristics of which are shown in Table 2. From the study by Polonsky et al .…”
Section: Methodsmentioning
confidence: 99%
“…From another study [34], investigating counterregulatory responses to hypoglycaemia in Type 2 diabetic patients before and after intensified metabolic control, only data after improved control are shown. In 12 studies [24–32,34,35,37], metabolic responses to hypoglycaemia were compared between Type 2 DM and healthy controls, which form the focus of this review.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not clear whether the presence of autonomic failure secondary to advanced diabetic neuropathy predisposes to hypoglycemia. A reduced glucagon response has been seen in patients with type 2 diabetes and autonomic neuropathy compared to those without autonomic neuropathy; however, it is possible that more advanced islet cell failure could have contributed to this as well [ 19 ].…”
Section: Risk Factors For Hypoglycemia In Patients With Diabetes and mentioning
confidence: 98%